Analisis Sistem Perkreditan dan Pembiayaan Pola Pengambe’ pada Wirausaha Penangkapan Ikan Skala Kecil di Muncar Jawa Timur - Adyla Mita Lestari; Juli Rahaju (STKIP PGRI SITUBONDO, 2023)
The existence and Role of Pengambe’(Money Lender) opten invokus a negative assumsiont , the lintah darat such that the Pengamba’ fungciont as a profiteer who exploits small scale of Fisherman. Becouse of this assumtiont, it is weedeply accepted the exintence of pengambe’, althougt the goverment has provided the fisherman with several opportunities to acces various other credit fasilities, the Result have been unsatisfactory and the Fisherman’s deppendence on the pengambe’ or other non formal means of credit has continued. This research aims to decribe the loan giving system of the pengamba’ to the Fisherman, dercribing sosiologycal factors with play a rule in the existence of pengembe; as a source of non formal credit.The result of this analisis will hoppelifully clarrify why this pengambe’ existwithin the smallscale fishing comunity and hoppely can be used by the goverment to formulatea credit policy for this fisherman. Apart from that, it is also hope to change the negative strereotype view of the public towards the rule of this pengambe